2014
DOI: 10.1007/s00220-014-2091-0
|View full text |Cite
|
Sign up to set email alerts
|

n-Particle Quantum Statistics on Graphs

Abstract: Abstract:We develop a full characterization of abelian quantum statistics on graphs. We explain how the number of anyon phases is related to connectivity. For 2-connected graphs the independence of quantum statistics with respect to the number of particles is proven. For non-planar 3-connected graphs we identify bosons and fermions as the only possible statistics, whereas for planar 3-connected graphs we show that one anyon phase exists. Our approach also yields an alternative proof of the structure theorem fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…The main advantage of this approach is that it allows to easily predict the results of many complex calculations. The method recovers all the known results concerning (co)homology groups of graph configuration spaces [14,23]. Its application to higher (co)homology groups, however, still requires considerable development.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…The main advantage of this approach is that it allows to easily predict the results of many complex calculations. The method recovers all the known results concerning (co)homology groups of graph configuration spaces [14,23]. Its application to higher (co)homology groups, however, still requires considerable development.…”
Section: Introductionmentioning
confidence: 58%
“…Recently the idea of Leinaas and Myrheim has been explored in the setting of graphs [14]. In particular, the authors of [14] showed that particles constrained to move on a graph can exhibit even more exotic forms of anyons.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations